MAGNESIUM, ZINC, AND COPPER IN SERUM, ERYTHROCYTE, URINE AND DIALYZATE FLUIDS OF HAEMODIALYSIS PATIENTS - N. Najem, Sami, (Iraqi Journal of Pharmaceutical Sciences, 2017)
Copper (Cu) Zinc (Zn) and Magnesium (Mg) in serum, RBC, urine and dialyzate fluids werestudied in 39 patients, who have been undergoing chronic haemodialysis treatment. They weredivided in to polyuric , oliguric and anuric depending on their urinary output. Elevated serum andRBC Mg was observed before dialysis, while decreased serum and RBC level was noticed exceptserum Mg of polyuric patients. Before dialysis elevated serum and RBC Zn were observed. Whileafter dialysis these parameters were increased. Normal RBC Cu value before dialysis was observed.While low serum Cu was noticed. After dialysis serum Cu showed raised value, while RBC leveldecreased in oliguric and increased in polyuric patients. Zn / Cu ratio found to be high in thosepatients. All these results were discussed in relation to urine content and also to the dialyzate fluid.Key words: Trace elements, Haemodialysis, Renal failure